Acute kidney injury in patients hospitalized with COVID-19 in HIMS, Hassan - R. M., Suresh; Kanchana; Begum, Kousar; B. S., Harsha (International Journal of Research in Medical Sciences, 2023)
Background: There is a growing need to understand the risk factors and prevalence of AKI in COVID-19 patients to better manage and prevent the condition. HIMS, Hassan is a hospital in India that has been treating COVID-19 patients since the onset of the pandemic. This study aimed to determine the prevalence of acute kidney injury (AKI) in COVID-19 patients admitted to a hospital in HIMS, Hassan, and to identify the associated risk factors. Methods: The study is a retrospective cohort study that investigates the clinical characteristics and laboratory parameters of hospitalized COVID-19 patients who met the inclusion criteria in HIMS teaching hospital, Hassan. 300 patients were included, and descriptive statistical analysis was performed using mean with standard deviation (SD) for continuous variables and proportions and percentages for categorical variables. Results: Out of 300 patients, 68% had AKI. The age distribution was similar between the two groups, with the highest proportion of patients in the age group of 40-49 years. The proportion of AKI was higher among males than females, but the difference was not statistically significant. The need for ICU admission, mechanical ventilation, and dialysis was strongly associated with AKI. Patients with comorbidities such as DM and DM+HTN were at a higher risk of developing AKI. Laboratory parameters such as D-dimer, LDH, ferritin, urea, creatinine, SGOT, SGPT, Neutrophils / Lymphocytes ratio, and chloride levels were significantly different between the two groups. Conclusions: These findings highlight the importance of monitoring patients with comorbidities closely and implementing preventive measures to reduce the incidence of AKI in COVID-19 patients.